2022
DOI: 10.1007/s11426-022-1304-1
|View full text |Cite
|
Sign up to set email alerts
|

A gating ultramicroporous metal-organic framework showing high adsorption selectivity, capacity and rate for xylene separation

Abstract: Adsorptive separation of p-xylene (pX) from xylene isomers is a key process in chemical industry, but known adsorbents cannot simultaneously achieve high adsorption selectivity, capacity, and rate. Here, we demonstrate gating ultramicropore as a solution for this challenge. Slight modification of the synthetic condition gives rise to isomeric metal-organic frameworks α-[Zn(pba)] (MAF-88, H 2 pba = 4-(1H-pyrazol-4-yl)benzoic acid) and β-[Zn(pba)] (MAF-89) possessing similar pillared-column structures, porositie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…PXRD data revealed that TPBD-αI had converted to TPBD-PX upon exposure to an equimolar quaternary mixture of C8 aromatic isomers within 35 min (Figure S58), indicating relatively fast kinetics under slurry-assisted immersion at room temperature. This sorption time is comparable to MOFs, PCPs, and PMCs with high selectivities. ,,, In the liquid phase, MAF-36 - 3C ( S PX/OX/MX = 51.3) and 3B ( S PX/OX/MX = 16) exhibited varying adsorption rates, taking 24 and 3 h, respectively, whereas form 1B ( S PX/OX/MX = 15) exhibited fast uptake in 2 min attributed to smaller crystal size .…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…PXRD data revealed that TPBD-αI had converted to TPBD-PX upon exposure to an equimolar quaternary mixture of C8 aromatic isomers within 35 min (Figure S58), indicating relatively fast kinetics under slurry-assisted immersion at room temperature. This sorption time is comparable to MOFs, PCPs, and PMCs with high selectivities. ,,, In the liquid phase, MAF-36 - 3C ( S PX/OX/MX = 51.3) and 3B ( S PX/OX/MX = 16) exhibited varying adsorption rates, taking 24 and 3 h, respectively, whereas form 1B ( S PX/OX/MX = 15) exhibited fast uptake in 2 min attributed to smaller crystal size .…”
Section: Resultsmentioning
confidence: 55%
“…These values surpass the selectivity of current benchmark sorbents MAF-36−3C (51.3 at 25 °C), 19 Mn-dhbq (48.3 at 120 °C), 31 and MAF-89 (46.4 at 35 °C). 20 Furthermore, while TPBD-αII (S PX/OX/MX = 43.6) displayed a slightly lower selectivity than previous benchmarks, its performance remains high (Figures 4a and S55). Concerning purification of PX from EB, literature reports are limited, likely reflecting that sorbents tend to exhibit relatively low PX/EB selectivity, making them unsuitable for purifying PX when EB is present.…”
Section: And Figures S44−s49)mentioning
confidence: 83%
See 2 more Smart Citations
“…Over the past decades, the great potential of energy-saving physical adsorption and separation technology has encouraged fast development of task-specific adsorbents, ,,,, and many porous solids, such as zeolites, , mesoporous silica, metal oxides, ionic microgels, activated carbons, and polymers, , have been tested for SO 2 adsorption. However, these traditional materials tend to show low SO 2 uptake capacities due to limited surface areas and porosities, high regeneration energy, and, even worse, irreversible structural degradation under harsh conditions required to remove adsorbed SO 2 .…”
Section: Introductionmentioning
confidence: 99%